MODEL INDUKTIF KATA BERGAMBAR TERHADAP KEMAMPUAN MANYUSUN KALIMAT ACAK S-P-O-K SISWA TUNARUNGU DI SDLB-B - Efiawanti Nandatiar, Fetri (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Hearing impairment had impact to the students’ speech ability. As a consequence, the hearing impairment students had hindrance to the communication process especially in arranging sentence ability which tended not to be suitable with SPOC pattern causing the sentence difficult to understand. This research purpose was to observe whether there was influence of inductive pictured words model toward arranging jumbled sentence SPOC ability to hearing impairment students in SDLB-B Karya Mulia I Surabaya or not. This research used quantitative approach of pre experiment research kind and this research arrangement was one group pre-test post-test design with 6 hearing impairment students of class III in SDLB-B Karya Mulia I Surabaya as the subjects. The data collection technique was in the form of test with the data analysis technique i.e. statistic non parametric using sign test formula. The result of data analysis indicated that there was significant influence of inductive pictured words model toward arranging jumbled sentence SPOC to hearing impairment students in SDLB-B Karya Mulia I Surabaya.   Keywords: Inductive pictured words model, arranging jumbled sentence SPOC